DEVELOPMENT OF DIGITAL MARKETING IN SMALL BUSINESSES (Marketing Journal, 2025)
The article examines the role of digital marketing in small business and entrepreneurship, and examines the factors contributing to the development of small businesses.
Keywords: digital transformation; business development; small business